Joining Parti Amanah Negara (Amanah) and Leaving Parti Islam seMalaysia (PAS): The Case Study of Amanah Party Activists in Terengganu - W.A.Ghapar, Wan Rohila Ganti; C.M.Razali, Che Hamdan (School of Social Sciences, USM, 2017)
Party activists are assets to the political party. Their contributions to the party in terms of time, money and energy are undeniable. They are the strongest supporters of the parties and candidates during elections, very loyal and dedicated to the party and research shows that the more active members a party has in a constituency, the more votes it will win there. This paper explores the factors that drive individuals to become political party activists of a newly established party, Parti Amanah Negara – Amanah (National Trust Party). Then it is followed by a discussion on why do they leave the party (Parti Islam seMalaysia – PAS) they once became very active. The discussions are mainly guided by the General Incentive theory that suggests seven incentives that motivate individuals to become party activists. The last part briefly analyses the future and prospects of Parti Amanah Negara in the next 14th General Election, specifically in Terengganu, the PAS stronghold state. The respondents reveal that ideological differences between them and the former party are too great and they are more skeptical about the value of political engagement through PAS. This study also opposes the existing literature that the tendency for ideologically-extreme activists to leave the party is lower compared to the moderate activists since all the respondents were former active PAS activists in Terengganu and had been with party for years.